Which spanish regions are falling further behind in entrepreneurship in the 2007-2019 period?. - Angulo-Guerrero, María José; Bárcena-Martín, Elena María; Medina-Claros, Samuel; Pérez-Moreno, Salvador Jesús (My University, 2024)
This study examines the extent to which Spanish regions are left behind in entrepreneurship between 2007-2019, comparing changes in the crisis period 2007-2014 and in the recovery period 2014-2019. To this end, we rely on the theoretical framework of the stages in the development of entrepreneurial activity provided by the Global Entrepreneurship Monitor (GEM). A fuzzy logic approach is applied to identify regions further left behind in entrepreneurial intentions, early-stage entrepreneurial activity and established business. Our findings display that the degree to which regions are left behind is particularly larger for entrepreneurial intentions and activity in 2014, showing the various impacts of the Great Recession on entrepreneurship across Spanish regions. Nevertheless, in both periods the changes in the degree to which regions are falling behind is pro-left behind regions, i.e., those regions left furthest behind at the beginning of the period were those that most reduced gaps with respect to better performing regions (quasi-β-convergence), even though with notably different patterns across regions. Likewise, despite these quasi-β-convergence processes in both periods, given the high re-ranking across regions over the crisis period, just in the recovery period the dispersion or inequality in the degree of falling behind across regions decreased (σ- convergence).
Keywords: Emprendedores - España; Disparidades regionales - España; Entrepreneurial intention and activity; Spanish regions; Inequality; Fuzzy approach; Convergence